Effect of Crocin on Cell Cycle Regulators in N-Nitroso-N-Methylurea-Induced Breast Cancer in Rats - Ashrafi, Mahboobeh (DNA Cell Biol, 2015)
We previously showed the anticancer effect of crocin, a saffron carotenoid, in both breast and gastric cancers in animal models, but its mechanism of action is not clearly known, yet. In this study, the effect of crocin on cell cycle regulators is investigated. Female Wistar Albino rats were divided into two groups, with or without N-nitroso-N-methylurea (NMU) injection. After tumor formation, each group of rats was divided into two subgroups, receiving crocin or vehicle only. After 5 weeks, the rats were sacrificed and the tumors were retained for pathologic investigation and determination of the parameters. Before crocin treatment, the tumor volumes were 13.27±3.77 and 12.37±1.88, but at the end of the experiment, they were 23.66±8.82 and 11.91±2.27 in the control and crocin-treated groups, respectively. Pathologic investigation indicated the adenocarcinoma induction by NMU. Reverse transcription–polymerase chain reaction and Western blot analysis showed overexpression of cyclin D1 and p21(Cip1) in the NMU-induced breast tumors; however, the expression of both of them suppressed by crocin treatment. The previous studies indicated that crocin induces apoptosis in tumor tissue. In this study, we show that it also suppresses tumor growth and induces cell cycle arrest by downregulation of cyclin D1. In addition, crocin suppressed p21(Cip1) in a p53-dependent manner.